Study on the influence of connection ring on the stability of assembly columns applied in demountable structures. (August 2021) - Liu, Cong; He, Lin; Yuan, Jian
Abstract: The aluminum alloy assembly column is a demountable component composed of four tubes and connection joints. The design of this column is based on the concept of assembling large components with small ones, which can be operated manually by one or two people. This paper presents influence of connection ring on the stability of assembly columns by experimental and numerical method. The axial stability tests were conducted to obtain the failure modes and strain distributions of columns. The numerical model, which was suitable for parametric analysis of the assembly column, was conducted. The ultimate strength and failure modes obtained from the test results validated the numerical predictions. The parametric analysis of columns with two connection rings was conducted, which identified the influences of connection ring spacing and tube spacing on ultimate bearing capacity of the assembly column. The optimal connection ring location was found. The quantitative calculation method of stability capacity of the column was obtained via the computation of thousands of models. The formula took the influences of the connection ring spacing, tube spacing and the column height into account, which could help guide the design of assembly columns and enlarge the scope of potential applications for demountable structures.